Private and Financial Sector Resilience in the Caribbean : 360° Resilience Background Paper - Masetti, Oliver (World Bank, Washington, DC, 2021)
The private sector in the Caribbean is crucial for economic growth and job creation and economic resilience is thus heavily determined by the shock absorbing capacity of individual firms and households. As the definition of the private sector is generally broad and includes economic agents of various size operating across different sectors, the assessment conducted in this chapter is multifaceted and considers different elements that determine vulnerabilities and resilience to exogenous shocks. The focus of the analysis is on the private sector’s vulnerability to tropical storms, the type of disaster most prevalent in the region, but the discussion of risks and vulnerabilities is also more broadly applied to other types of shocks, such as the COVID-19 pandemic.